2022
DOI: 10.3390/ijerph19063443
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Peri-Implant Bone Loss with a Convergent Transmucosal Morphology: Retrospective Clinical Study

Abstract: Objective: The aim of this study was to analyze the peri-implant bone loss of infracrestal, supracrestal, and crestal implants from the day of placement and up to 1 year of prosthetic loading. Material and methods: A retrospective clinical study was carried out. The sample consisted of 30 implants placed on 30 patients. It was divided into three groups: infracrestal (n = 10), crestal (n = 10), and supracrestal (n = 10) implants. Results: Following the statistical analysis, it was observed that, 4 months after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…To date, the only data available on this implant design are from single-implant rehabilitations, which are difficult to compare due to the numerous differences regarding several aspects of the rehabilitation, including the surgical and prosthodontic protocols applied and the parameters recorded. In a one-year clinical study, Castillo et al [ 29 ] concluded that implants with transmucosal convergent collars were prone to less bone resorption when compared to implants with a cylindrical transmucosal neck. Canullo et al [ 30 ] compared tissue level implants to traditional bone level implants in the rehabilitation of a single missed tooth in the aesthetic area up to 5 years of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the only data available on this implant design are from single-implant rehabilitations, which are difficult to compare due to the numerous differences regarding several aspects of the rehabilitation, including the surgical and prosthodontic protocols applied and the parameters recorded. In a one-year clinical study, Castillo et al [ 29 ] concluded that implants with transmucosal convergent collars were prone to less bone resorption when compared to implants with a cylindrical transmucosal neck. Canullo et al [ 30 ] compared tissue level implants to traditional bone level implants in the rehabilitation of a single missed tooth in the aesthetic area up to 5 years of follow-up.…”
Section: Discussionmentioning
confidence: 99%